SUSTAINABILITY IN THE SUPPLY CHAIN: benefits and challenges - Cumim, Rogério Matheus; Santos, Marcio Cristian Sandro dos (Revista Interface Tecnológica, 2025)
Sustainability is a recurring and highly researched topic in recent times due to its significant impact on society and its strong influence on the image of companies. These factors reveal that organizations are not independent but are integrated into the society in which they operate, making sustainability in the supply chain an indispensable action. Within this dynamic, companies find themselves needing to develop sustainability comprehensively to meet all stakeholders' demands. In this context, the objective of this study was to analyze sustainability in the supply chain, its benefits, and its challenges. The research model used was bibliographic, through the exploration of academic articles, websites, digital magazines, and scientific works. The results show the challenge companies face in the relationships between the involved links and the social, environmental, and economic benefits, leading to the improvement of human protagonism and well-being, as well as waste reduction and cost savings.
Keywords: Sustainability; Supply chains; Benefits. Challenges